MOOCs Changing Behavior: New Challenges and Issues Leads to Opportunity - et.al, Neha Yadav (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Learning through distance mode very helpful for all of us nowdays. MOOCs plays very important roe in all aspects. Govt of india also launch so many platform for this type of various learning domain. Learning were also early incarnations of varios factors depends of nature of learning in the form of written distance learning. MOOCs are a recent development in online education and have several distinctive features compared to previous distance education models. MOOCs are online courses intended for massive interactive participation and free web access. Materials of many conventional course such as powerpoint presentations, online notes, readings, quizzes, and videos. MOOCs provide very interactive and formation of collaborative learning forums that will be very helpful to build community for students and teachers